Characterization of an Intravenously Injected Bolus - Samuel, A. M.; Raikar, U. R.; Atmaram, S. H.; Ganatra, R. D. (Nuklearmedizin - NuclearMedicine, 1976)
A study of some parameters affecting the time activity histogram of an intravenous bolus injection of radioactivity was performed. A scoring system for bolus compactness was attempted. A score of 2 and above was considered to be a satisfactory bolus. Volumes less than 1 ml tended to result in a satisfactory bolus. The nature of radiopharmaceutical injected, different injecters and age of the patient did not affect the score. Thyrotoxic patients gave the best bolus score.